The Perception of Employees on the Mandatory Pension Savings in Case of Kosovo - Mustafi, Besime (Journal of Danubian Studies and Research, 2023)
The stability of pension fund is very important for social welfare in general and for a sustainable economic development in particular. The main purpose of this study is to analyse the perception of employees on the mandatory pension savings in the case of Kosovo. Examining local and international literature, the method used in this study is the online questionnaire with a sample of 300 respondents employed in the private and public sector. The collected data were processed and tested through the IBM SPSS program where the descriptive analysis, frequencies, the cross-tabulation tables, Pearson correlation and Chi-Square test are used and presented in the study. The paper concludes that employees, regardless of age, the level of education and the sector in which they work, do not have any perception related mandatory pension savings in general. The result of Chi-Square Test also proves that the variables under analysis respondents’ level of education and their perception to the right of the state to compulsory pension are not related to each other. The paper comes with some others conclusions and recommendations based on research findings.